Defective serum opsonization activity in children aged 6-48 months having acute purulent otitis media - Tezcan, İlhan and Yılmaz, Yeşim and Öner, Filiz and Yel, Leman and Sanal, Özden and Ersoy, Fügen and Önerci, Metin and Berkel, A. İzzet (The Turkish Journal of Pediatrics, 1997)
Serum opsonization of yeast (Saccharomyces) was investigated in 51 patients whose ages were between six and 48 months (median 15 months) with acute purulent otitis media and in an age-matched control group (median 13 months). Opsonization was assessed by measuring yeast particle uptake in an assay based on an electronic count of the unphagocytosed particles in serum by polymorphonuclear leukocytes. Despite normal levels of CH50 and serum immunoglobulins, a defective opsonization was determined in 13.7 percent of the patients (7 in 51). The corresponding figure was 2.9 percent in 103 healthy controls (p < 0.001). On the other hand, 218 percent (5 in 23) of the children having a history of recurrent purulent otitis media showed defective opsonization (p < 0.001). Previously, the presence of an opsonization defect has been linked to low levels of mannan binding lectin (MBL), a calcium dependent serum lectin that acts as an opsonin. Therefore, our findings indirectly support the idea that MBL has an important role as host defense, particularly in the earlier period of life when the antibody repertoire is restricted.